Role of novel serum brain specific biomarkes in prognosis of patients with acute neurological insults - Mohamed Omar Elghonemi; Amany Mahmoud Rabbah; Kofke Andrew; Wahid Ahmed Radwan (Cairo : Mohamed Omar Elghonemi, 2013)
One of the main drawbacks in the management of patients with acute brain injuries is the absence of a widely available and rapid diagnostic test . The objective of our study was to assess whether Phosphorylated Neurofilament H (pNF-H) might provide useful diagnostic information in the early evaluation of such patients and weather levels of the neurofilament correlated with different clinical variables
Thesis (Ph.D.) - Cairo University - Faculty of Medicine - Department of Critical Care Medicine
Issued also as CD
Keywords: Acute brain insults; Ischemic CVS Cerebral Hge; Neurofilaments